Treatment strategies for enhancing the removal of endocrine-disrupting chemicals in water and wastewater systems - Zamri M.F.M.A.; Bahru R.; Suja' F.; Shamsuddin A.H.; Pramanik S.K.; Fattah I.M.R. (Elsevier Ltd, 2023)
The emergence of endocrine-disrupting chemicals (EDC) in water and wastewater systems has high-risk implications for the environment. This manuscript discusses the treatment strategies for the removal of EDC in water and wastewater systems. The reviewed treatment outlines for EDC removal are classified into physical, biological, and chemical treatments. The application of EDC treatments is discussed based on the removal and degradation process to eliminate the EDC compounds. Interestingly, the physical treatment of membrane filtration processes has been an efficient method for EDC removal without using chemical disinfection in a treatment system. Nevertheless, like other EDC treatment methods, the membrane filtrations are not able to remove emerging contaminants completely. Thus, the overall factor of limitations and challenges in EDC treatment methods such as solubility, hydrophilicity, degradability, and polarity are discussed as to understand the applicability of the treatment techniques from the degradation pathways and the by-products produced. The integration treatment strategies through alternative approaches, such as sequential and hybrid treatments that enhanced the considerable removal of EDC are rely on the sample characteristics. Therefore, this article gathered each treatment approach's effectiveness and limitations, providing a potential outlook of EDC treatment strategies in water and wastewater treatment systems. 2021 Elsevier Ltd